Résolution des équations de Saint-Venant par la méthode des volumes finis non structurés - Shi, Yu-e; Nguyen, Kim Dan; Nguyen, The Hung (European Journal of Computational Mechanics, 2007)
This paper presents a resolution of the Saint-Venant equations by a projection method. Using unstructured finite-volumes methods, a 2-D horizontal shallow water numerical model is developed. Two applications with complex bathymetries are reported in this article. The model can be applied to the calculation of river, estuarine and coastal flows.